The complete chloroplast genome of Tibetan medicinal plant Rubus phoenicolasius Maxim. Issue 3 (4th March 2021) - Zhang, Guoying; Liu, Yarong; Hai, Ping
Abstract: Rubus phoenicolasius Maxim. is a traditional Tibetan medicine and widely used in the clinical pharmacology. In current study, the complete chloroplast genome of R. phoenicolasius was reported. The total length of the genome was 155, 144 bp with the GC content of 37.9%. We predicted 130 genes in the genome including 84 protein-coding genes, 37 tRNA genes, 8 rRNA genes and 1 pseudogene. 17 genes were duplicated in the IR regions including 7 tRNA, 4 rRNA and 6 protein-coding genes. Phylogenomic analysis revealed that R. phoenicolasius forms a strong supported branch with R. amabilis and R. coreanus under the Rosaceae clade.